Measuring the future of NFT as digital asset in realizing economic revitalization - Rodrikson Alpian Medlimo; Aisya Dyas Septania; Hardina Okteviara Hapsari; Muhammad Fariel Zuleika; Tasya Agustin (Goodwood Publishing, 2022)
Purpose: Indonesia is a democratic country based on the principles of justice, togetherness and balance as the goals of the state as stated in the 4th paragraph of the 1945 Constitution. In this regard, the development of creative industries that are oriented towards the fulfillment of social welfare within the framework of shared prosperity becomes a fundamental basis in the practice of life. Research Methodology: The author uses a normative juridical research method that is descriptive analysis. Data collection is done through literature study and the data used in this paper is secondary data obtained through library materials collected through literature study, then analyzed qualitatively to obtain writing conclusions. Results: The results show that digital asset transformation is an extensive, instrumental and comprehensive approach to respond to technological disruption, especially in the era of society 5.0. Limitations: The dimensions of life are required to be adaptive to the times, associated with the current Covid-19 Pandemic situation. The pandemic has become a disruptive momentum due to the movement of global supply chains into digital and virtual spaces, such as in buying and selling goods and services, as well as interpersonal interactions. Contribution: With the fantastic number at the digital market in Indonesia, collaboration of all parties must be implemented in achieving the vision, mission and goals of business development through the use of NFT (Non-Fungible Token) as a digital asset. In solving the various challenges of NFT in Indonesia, the author phenomenologically initiates the importance of “pentahelix” synergy in educating the public that NFT can be developed as a business instrument.